Analysis of Students' Literacy Skills in Identifying Intrinsic Elements of Moral Values in Folktales at Elementary Schools - Sari, Ersi Mutia; Sapri, Sapri (UNIVERSITAS PAKUAN, 2023)
The research was conducted at Elementary School 112321 Kampung Pajak. The aim of this study was to assess students' literacy skills in analyzing the intrinsic elements and moral values in folktales